Menelisik Kesehatan Bank Menggunakan Metode Risk Based Bank Rating - Yasmir Yasmir (Universitas Pendidikan Nasional, 2020)
The purpose of this study is to determine the health level of the Bank Pembangunan Daerah Jambi in 2015-2019. The object of research is the Regional Development Bank, one of which is an active role in increasing the development of each area where the shares are owned by the provincial government, based on Article 2 Number 13/1 / PBI. / 2011 point 2, Banks are required to conduct a soundness rating using a risk-based bank rating, both individually and on a consolidated basis. The results of the analysis of banking financial ratios using Risk Based Bank Rating indicate the condition of the financial performance of PT. Bank Pembangunan Daerah Jambi 2015-2019 from the aspect of Risk Profile NPL ratio meets bank standards except the Loan to Deposit Ratio does not meet the standards set by Bank Indonesia. In GCG analysis, which is an assessment of the quality of bank management on the implementation of GCG principles that has met bank standards. in the profitability ratio analysis, financial performance conditions can be said to be very good. In the analysis, the capital adequacy ratio has met Bank Indonesia's standards.